How Does the Canadian General Public Rate Moderate Alzheimer's Disease? - Jean-Eric Tarride; Mark Oremus; Eleanor Pullenayegum; Natasha Clayton; Parminder Raina (Journal of Aging Research)
Objectives. The objectives of this study were to elicit health utility scores for moderate Alzheimer's disease (AD) using members of the general public. Methods. Five-hundred Canadians were chosen randomly to participate in a telephone interview. The EQ-5D was administered to estimate the health utility score for respondents' current health status (i.e., no AD) and for a hypothetical moderate AD health state. Regression analyses were conducted to explain the perceived utility decrement associated with AD. Results. The mean age of the respondents was 51 years, 60% were female, and 42% knew someone with AD. Respondents' mean EQ-5D scores for their current health status and a hypothetical moderate AD were 0.873 (SD: 0.138) and 0.638 (SD: 0.194), respectively (P<0.001). Age, gender, and education were significant factors explaining this decrement in utility. Conclusion. Members of the general public may serve as an alternative to patients and caregivers in the elicitation of health-related quality of life in AD.